Humor translation from Spanish into English -of the movie "Asumare" - Guaylupo Polo, José Antonio Emanuel (2018)
The main objective of this research was to determine the  elements that  hinder the  translatability of the humor of the Spanish to English in the scenario  of the film "Asu Mare" Trujillo 2015. El type of study  is focused  on the  under- standing, design,  was the  study  of cases.  Was used as an instrument of collection of information the registration form; two basic techniques of analysis was used for the analysis of information collected from field: analysis of contents to transcribe scenes  from the film 'Asu Mare'  and domain analysis to translate all the information collected.  From  this study, it can be concluded that:  there  are at least seven  difficulties  to for the  translatability of humor,  these  are semantic,  syntactic,  morphological, lexical  ordering, pragmatic, phonetic and physiotherapy. Not all the elements that make it difficult for the translatability of humor are  translatable; on  some occasions,  it is necessary to resort to the adaptation of a term from one language to another so as to not lose the original sense of humor.  This, in turn,  has manifested itself most often in elements that hinder the translatability of humour or phonetic level and physiotherapy, which should  be noted,  they were not included in the present study,  but  they  played  a fundamental role at the time of analyzing  the translatability of humor.  Keywords: humor, movie,  translatability, lexical and morphological.